Handbook of British romanticism - Haekel, Ralf (Handbooks of English and American studies, 2017)
"The Handbook of British Romanticism is a state of the art investigation of Romantic literature and theory, a field that probably changed more quickly and more fundamentally than any other traditional era in literary studies. Since the early 1980s, Romantic studies has widened its scope significantly: The canon has been expanded, hitherto ignored genres have been investigated and new topics of research explored. After these profound changes, intensified by the general crisis of literary theory since the turn of the millennium, traditional concepts such as subjectivity, imagination and the creative genius have lost their status as paradigms defining Romanticism. The handbook will feature discussions of key concepts such as history, class, gender, science and the use of media as well as a thorough account of the most central literary genres around the turn of the 19th century. The focus of the book, however, will lie on a discussion of key literary texts in the light of the most recent theoretical developments. Thus, the Handbook of British Romanticism will provide students with an introduction to Romantic literature in general and literary scholars with a discussion of innovative and groundbreaking theoretical developments"--Provided by publisher